Occupational history of night shift work and Parkinson's disease in Denmark - Eva S Schernhammer; Christina Funch Lassen; Line Kenborg; Beate Ritz; Jørgen H Olsen; Johnni Hansen (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVES: We investigated whether working night shifts was associated with the risk of Parkinson's disease (PD). METHODS: Between January 2008 and December 2010, we recruited 1808 patients with a confirmed diagnosis of idiopathic PD from Denmark and 1876 population controls matched by year of birth and gender. Information on lifelong occupational history, including information on night work, smoking, caffeine and alcohol consumption habits, and family history of PD was collected through structured telephone interviews. RESULTS: Overall, there was no association between a history of night shift work and PD [odds ratio (OR) for any type of night work (ie, either permanent or rotating night work) 1.01, 95% confidence interval (95% CI) 0.86-1.21]. Compared with persons who never worked night shifts, risks of those with longer durations of night work did not appear to differ (OR_<10 years=0.95, 95% CI 0.75-1.19, OR_10-19 years= 1.09, 95% CI 0.77-1.53, OR_≥20 years=1.05, 95% CI 0.81-1.37, P for trend=0.23). Associations were similar among men and women. CONCLUSIONS: These data suggest that working night shifts is not associated with PD or that low tolerance for night shift work is an early marker of PD. Due to the novel and exploratory nature of these findings, confirmation is needed.